Consolidation behavior of Mo30W alloy using spark plasma sintering. (April 2022) - Gaffin, Neal D.; Ang, Caen; Milner, Justin L.; Palomares, Kelsa B.; Zinkle, Steven J.
Abstract: Molybdenum alloys are excellent candidates for extremely high temperature environments, such as in nuclear thermal propulsion spaceflight systems. Spark plasma sintering is a useful manufacturing technique that allows for rapid fabrication of refractory materials that are difficult to sinter using more traditional methods. Pre-alloyed molybdenum with 30 wt% tungsten powder was consolidated using spark plasma sintering under a variety of conditions to determine the optimum sintering conditions. Hold temperatures between 1400 and 1700 °C, at sintering pressures from 10 to 50 MPa, and for hold times at maximum temperature from 0.5 to 90 min were tested. The effects of hold temperature, sintering pressure, and hold time on the microstructure and mechanical properties were examined. Higher applied pressures are necessary to achieve higher sample density at lower temperatures. Sintered densities ranging from 88.8 to 97.9% theoretical were achieved over the testing conditions, with the highest density being achieved with sintering conditions of 1700 °C and 50 MPa for 5 min. The hardness of the sintered material followed the Hall-Petch inverse grain size relationship over the investigated grain sizes. Grain growth at 1600 °C was found to follow a second order relationship with time. When compared with pure molybdenum, solid solution strengthening was observed to increase the hardness of the alloy. From these experiments and analysis, an understanding of how sintering conditions affect the density and microstructure of the alloy was developed that will allow for future development of ceramic metallic composite materials for nuclear thermal propulsion. Highlights: Mo30W sintered to greater than 97% theoretical density using SPS. Grain growth of Mo30W alloy follows a second order power law. Mo30W follows Hall-Petch relationship with ky of 490, less than pure Mo and W. Strength and hardness model derived and fit for isothermal sintering.